Unidirectional and Selective Proton Transport in Artificial Heterostructured Nanochannels with Nano-to-Subnano Confined Water Clusters - Li, Xingya (Advanced materials (Deerfield Beach, Fla.), 2020)
© 2020 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.